Tax Residence under UAE Legislation - Idelbi, Mona (Journal of Legal Sciences, 2025)
The tax law, like other laws, is a manifestation of state sovereignty, as each state exercises all its powers within the scope of its territory without exceeding the borders of other, which is expressed in the principle of territoriality of the tax law, This means that every country cannot impose its taxes outside its borders, this thing may be a natural in the past where the activity of individuals did not pass the borders of their countries, but under the economic development and the activation of trade exchange between countries and investments which exceeding the borders of regions, and the emergence of the multinational companies, all of these made The world as one village, so it will be necessary to determine the tax domicile differently, according international standards, because it related to huge revenues that countries may lose as a result of applying the old concept . It is also necessary to point out the weak points in this regard, which the legislator must reconsider and amend to ensure proper implementation of the law to achieve its goals at all levels. The Emirati legislator has stipulated this in the Tax Procedures Law and its Executive Regulations, as well as in the Corporate and Business Tax Law, and in multiple administrative regulations, so it will be necessary to prepare a comprehensive study of all the provisions of tax domicile in accordance with Emirati legislation, especially UAE is one of the most important investment destinations in the world.